Pengaruh Penambahan Biovet dalam Ransum dengan Berbagai Kandungan Protein-Energi terhadap Pertumbuhan Anak Kelinci Rex - D Aritonang; B Tj Hariadi; Y C Raharjo (Media Peternakan, 2004)
An experiment was conducted to study the effect of Biovet supplement in diets of different protein-energy to weight gain of Rex rabbit kit. The experiment used 112 kit of 28 Rex Rabbits at PT Fiva Bandung Rabitry, Pangkalan village, Sub districk Gambung-Ciwidey District Bandung in Completely Randomized Design 7 treatments and 4 replications. The treatments were: R0: 18% CP and 2750 kcal/kg; DE R1: 16% CP, 2500 kcal/kg DE + 0% Biovet; R2: 16% CP, 2500 kcal/kg DE + 0,1% Biovet; R3: 16% CP, 2500 kcal/kg DE + 0,5% Biovet; R4: 14% CP, 2400 kcal/kg DE + 0% Biovet; R5: 14% CP, 2400 kcal/kg DE + 0,1% Biovet; and R6: 14% CP, 2400 kcal/kg DE + 0,5 % Biovet. Results showed that body weight gain, feed consumption, and conversion were similar to rabbits given biovet supplement in low quality diet. Key words: rabbit, biovet, protein-energy